2008
DOI: 10.1105/tpc.108.058628
|View full text |Cite
|
Sign up to set email alerts
|

NIP6;1 Is a Boric Acid Channel for Preferential Transport of Boron to Growing Shoot Tissues inArabidopsis

Abstract: Boron (B) in soil is taken up by roots through NIP5;1, a boric acid channel, and is loaded into the xylem by BOR1, a borate exporter. Here, the function of Arabidopsis thaliana NIP6;1, the most similar gene to NIP5;1, was studied. NIP6;1 facilitates the rapid permeation of boric acid across the membrane but is completely impermeable to water. NIP6;1 transcript accumulation is elevated in response to B deprivation in shoots but not in roots. NIP6;1 promoter–β-glucuronidase is predominantly expressed in nodal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
223
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(237 citation statements)
references
References 51 publications
14
223
0
Order By: Relevance
“…This is also supported by the fact that when Lsi6 was knocked out, the translocation of silicon to the panicles was greatly reduced ( Figure 4A). Recently, a boric acid channel from Arabidopsis thaliana (NIP6;1) was reported to be involved in the preferential transport of boron to growing shoot tissues (Tanaka et al, 2008). However, NIP6;1 is located at the phloem especially at the nodal region of the stem and petioles, suggesting that NIP6;1 is responsible for the xylem-phloem transfer of boric acid (Tanaka et al, 2008) but not for the intervascular transfer.…”
Section: Discussionmentioning
confidence: 92%
“…This is also supported by the fact that when Lsi6 was knocked out, the translocation of silicon to the panicles was greatly reduced ( Figure 4A). Recently, a boric acid channel from Arabidopsis thaliana (NIP6;1) was reported to be involved in the preferential transport of boron to growing shoot tissues (Tanaka et al, 2008). However, NIP6;1 is located at the phloem especially at the nodal region of the stem and petioles, suggesting that NIP6;1 is responsible for the xylem-phloem transfer of boric acid (Tanaka et al, 2008) but not for the intervascular transfer.…”
Section: Discussionmentioning
confidence: 92%
“…Arsenite is the predominant form of arsenic (As) in paddy soils. It has previously been suggested that aquaporins may have a role in boron transport in higher plants (Dordas et al 2000, Fitzpatrick and and it was also shown in Arabidposis thaliana that a specific NIP subclass aquaporin gene (AtNIP5;1) is required for normal growth under B limiting conditions (Takano et al 2006, Tanaka et al 2008. NIP5;1 is strongly up-regulated in B-deprived roots and knockout mutants for this gene are defective in low Binducible boric acid uptake into roots (Takano et al 2006).…”
Section: B Tolerance In Barleymentioning
confidence: 99%
“…Takano et al (2006) identified nodulin26-like intrinsic protein5;1 (NIP5;1) in Arabidopsis as a boric acid channel required for efficient uptake into root cells under B-limited conditions. Arabidopsis NIP6;1, the gene most similar to NIP5;1, contributes to the preferential distribution of B in young shoot tissues (Tanaka et al, 2008).…”
mentioning
confidence: 99%